Cost Efficiency Analysis To Maintain The Sustainability of Tobacco Farming in Grujugan Village, Bondowoso Regency - Atikah, Siti; Juanda, Ahmad; Leniwati, Driana (Riset Akuntansi dan Keuangan Indonesia, 2024)
This study aims to analyze cost efficiency in tobacco farming in Grujugan Village, Bondowoso Regency, and identify the factors influencing the sustainability of such farming practices. The methodology includes direct observation and interviews with experienced tobacco farmers. The results of the analysis indicate that cost efficiency is a key factor in enhancing profitability and sustainability in tobacco farming. Cost reduction can be achieved through the selection of superior varieties, the implementation of modern technology, and efficient resource management. Additionally, the importance of training for farmers in sustainable agricultural practices is identified as a strategic step to improve productivity. Despite facing climatic challenges, such as extreme dry seasons, the combination of these approaches can help tobacco farmers in Grujugan Village maintain and improve their farming outcomes, while also ensuring local economic sustainability.